Application of magnetic nanocomposite as adsorbent in removal of organic dye in water

By adding aniline inhibitors in the preparation process of magnetic nanocomposites, the crystallinity and porosity of magnetic COFs materials are improved, and the problem of low adsorption efficiency of magnetic COFs materials in the prior art is solved, thus realizing the organic dyes in water Highly efficient adsorption and good reusability.

CN119386827APending Publication Date: 2025-02-07ZHEJIANG MEDICAL COLLEGE
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202410681308.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, the magnetic COFs materials have poor crystallinity and low porosity, which leads to their low adsorption efficiency in removing organic dyes in water.

Method used

By adding aniline as an inhibitor in the preparation of magnetic nanocomposites, the reversibility of imine bonds is increased, thereby generating magnetic COFs materials with high crystallinity and high porosity. Specific steps include uniformly dispersing the aldehyde and amino monomers with the Fe3O4 magnetic core under ultrasound, adding a catalyst and aging in an oil bath, followed by magnetic separation and drying.

Benefits of technology

The magnetic nanocomposites Fe3O4@TAPT-OMePDA and Fe3O4@TAPT-TFPDA are realized with high efficiency adsorption of the organic dye Congo red in water, with an adsorption capacity of 1603.54 mg/g and 1968.83 mg/g, and the adsorption is in line with the quasi-secondary kinetic model and Langmuir isothermal model has high porosity, high adsorption efficiency, good selectivity and good reuse rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386827A_ABST
    Figure CN119386827A_ABST
Patent Text Reader

Abstract

The invention discloses application of a magnetic nano composite material as an adsorbent in removal of organic dye in water, and belongs to the technical field of application of composite materials, the magnetic nano composite material (one of Fe3O4-coated TAPT-OMePDA or Fe3O4-coated TAPT-TFPDA) as the adsorbent adsorbs the organic dye in water, the adsorption capacity of Congo red (CR) reaches up to 1603.54 mg / g and 1968.83 mg / g, and the adsorption capacity of the magnetic nano composite material (one of Fe3O4-coated TAPT-OMePDA or Fe3O4-coated TAPT-TFPDA) as the adsorbent adsorbs the organic dye in water. The adsorption of the two adsorbents to the CR accords with a quasi-secondary kinetic model and a Langmuir isotherm model, and belongs to single-layer chemical adsorption. Compared with an adsorbent in the prior art, the Fe3O4 (at) TAPT-OMePDA and the Fe3O4 (at) TAPT-TFPDA have the advantages that the porosity is high, the adsorption efficiency is high, the selectivity is good, and the repeated utilization rate is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite material applications, and in particular to an application of a magnetic nano composite material as an adsorbent in removing organic dyes from water. Background Art

[0002] Organic dyes usually have stable aromatic structures, are difficult to degrade in the natural environment, and have carcinogenic and mutagenic effects on organisms, which may cause major health and environmental problems. At present, the methods commonly used to remove organic dyes from water bodies include adsorption, photochemical oxidation, electrochemical, ozone oxidation, Fenton oxidation and microbial degradation. Among them, the adsorption method has the advantages of simple operation, low cost and low equipment requirements, and is one of the most easily implemented pollutant treatment methods. The core of the adsorption method is the adsorbent. Commonly used adsorbents include zeolite, activated carbon, metal oxides, organic-inorganic hybrid materials and metal-organic frameworks (MOFs). Among them, traditional adsorbents such as zeolite and activated carbon have low adsorption efficiency and limited regeneration capacity. As a new type of adsorbent, MOFs have insufficient coordination bond strength, resulting in insufficient stability. Generally, efficient adsorbents must have high adsorption capacity, high specific surface area, excellent thermochemical durability, excellent selectivity, low price, and excellent reusability and regeneration ability. Therefore, finding high-performance adsorbent materials is a direction worth exploring.

[0003] Covalent organic frameworks (COFs) are a class of crystalline porous organic polymers with periodic structures connected by covalent bonds (CC, CN, BO, etc.). In recent years, organic covalent frameworks (COFs) have been widely used in the field of adsorption and removal of organic dyes due to their large specific surface area, good chemical stability, regular pores and easy modification. As adsorbents, COFs can effectively adsorb organic pollutants through pore size effects, hydrogen bonds, π-π interactions, hydrophobic interactions and electrostatic interactions.

[0004] Currently, most COFs are prepared by traditional solvothermal synthesis, but the crystallinity problem is a challenge in COFs material research. The key step in COFs crystallization is to form ordered, defect-free crystals. By increasing the reversibility of covalent bonds during the reaction, the self-correction of crystal structure defects can be effectively carried out, thereby improving the crystallinity of the material. There are no reports on the synthesis of highly crystalline magnetic COFs composites. Summary of the invention

[0005] The embodiment of the present invention provides an application of a magnetic nanocomposite material as an adsorbent in removing organic dyes from water to solve the problems of poor crystallinity and low porosity of magnetic COFs in the prior art. The content of the present invention is as follows:

[0006] The object of the present invention is to provide a magnetic nanocomposite material for use as an adsorbent in removing organic dyes from water, and the technical point is that the magnetic nanocomposite material is one of Fe3O4@TAPT-OMePDA and Fe3O4@TAPT-TFPDA.

[0007] The second object of the present invention is to provide a method for preparing a magnetic nanocomposite (COFs) material as an adsorbent, the specific steps of which are as follows:

[0008] The aldehyde monomer and the amino monomer are placed in a 100 mL pressure-resistant bottle, o-dichlorobenzene and n-butanol are added as reaction solvents, and aniline is added as an inhibitor after being uniformly dispersed by ultrasonication for 5-15 minutes. Fe3O4 is added as a magnetic core, and Fe3O4 is uniformly dispersed by ultrasonication for 10-30 minutes. The present application increases the reversibility of imine bond formation by adding aniline competitive inhibitor, thereby generating a magnetic COFs material with high crystallinity and high porosity;

[0009] Fe(NO3)3·9H2O was ultrasonically dissolved in n-butanol as a catalyst, and then added to the pressure bottle reaction system in batches after dissolution, and ultrasonically reacted for 1 hour, and then aged in an oil bath at 80-120°C for 24 hours;

[0010] After the reaction, the mixture was separated by magnetic separation, washed twice with ethanol by ultrasonic wave for 20-40s, then washed twice with water by ultrasonic wave for 20-40s, then washed once with ethanol by ultrasonic wave for 20-40s, then washed twice with tetrahydrofuran by ultrasonic wave for 20-40s and washed once with n-hexane by ultrasonic wave for 20-40s;

[0011] Finally, the mixture is immersed in n-hexane for 20-40 minutes, and the solid product is dried in a vacuum drying oven at 50-70° C. for 4-6 hours to obtain the magnetic nanocomposite material.

[0012] In order to better realize the above technical scheme, in the preparation method of a magnetic nanocomposite material used as an adsorbent of the present invention, the aldehyde monomer is one of 2,5-dimethoxyterephthalaldehyde and 2,3,5,6-tetrafluoroterephthalaldehyde.

[0013] In order to better realize the above technical scheme, in the preparation method of a magnetic nanocomposite material as an adsorbent of the present invention, the amino monomer is 2,4,6-tris(4-aminophenyl)-1,3,5-triazine.

[0014] In order to better realize the above technical scheme, in the preparation method of a magnetic nano-composite material as an adsorbent of the present invention, the amount of aldehyde monomer (mmol), the amount of amino monomer (mmol), the amount of aniline (mmol), the amount of Fe(NO3)3·9H2O (mmol), the mass of Fe3O4 (g), the volume of o-dichlorobenzene (mL) and the volume of n-butanol (mL) are in the ratio of 0.3:0.2:0-1:0.06:0.15:15:15.

[0015] In order to better realize the above technical scheme, the purity of 2,5-dimethoxyterephthalaldehyde in the preparation method of a magnetic nano-composite material used as an adsorbent of the present invention is 97%.

[0016] In order to better realize the above technical scheme, the purity of 2,3,5,6-tetrafluoroterephthalaldehyde in the preparation method of a magnetic nanocomposite material used as an adsorbent of the present invention is 98%.

[0017] In order to better realize the above technical scheme, in the preparation method of a magnetic nano-composite material used as an adsorbent, the purity of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine is 95%.

[0018] In order to better realize the above technical scheme, the present invention provides a method for preparing a magnetic nanocomposite material as an adsorbent, in which the purity of aniline is AR, the purity of o-dichlorobenzene is 98%, the purity of n-butanol is ACS, and the purity of Fe(NO3)3·9H2O is 99.9% metals basis.

[0019] At least one of the above technical solutions adopted in the embodiments of the present invention can achieve the following beneficial effects:

[0020] The present invention provides an application of a magnetic nanocomposite material as an adsorbent in removing organic dyes from water. The magnetic nanocomposite material (one of Fe3O4@TAPT-OMePDA or Fe3O4@TAPT-TFPDA) is used as an adsorbent to adsorb organic dyes in water. The adsorption capacity of Congo red (CR) is as high as 1603.54 mg / g and 1968.83 mg / g. The adsorption of CR by the two adsorbents conforms to the pseudo-second-order kinetic model and the Langmuir isotherm model, and belongs to single-layer chemical adsorption. Compared with the adsorbents in the prior art, Fe3O4@TAPT-OMePDA and Fe3O4@TAPT-TFPDA have high porosity, high adsorption efficiency, good selectivity, and good reuse rate, which has practical reference significance for the actual treatment of printing and dyeing wastewater in the future. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1SEM images of magnetic COFs materials synthesized with different inhibitor dosages (0, 1, 2, 3, 4 and 5 equivalents respectively);

[0022] Figure 2 XRD patterns (a), nitrogen adsorption-desorption isotherms (b), and adsorption performance of CR (c) for Fe3O4@TAPT-OMePDA synthesized with different inhibitor dosages;

[0023] Figure 3 SEM images and XRD patterns of magnetic COFs materials synthesized at different aging temperatures;

[0024] Figure 4 SEM images and XRD patterns of magnetic COFs materials obtained from different monomers;

[0025] Figure 5 SEM images of Fe3O4@TAPT-OMePDA (left) and Fe3O4@TAPT-TFPDA (right).

[0026] Figure 6 Infrared spectra of Fe3O4@TAPT-OMePDA (left) and Fe3O4@TAPT-TFPDA (right);

[0027] Figure 7 Water contact angles of Fe3O4@TAPT-OMePDA (left) and Fe3O4@TAPT-TFPDA (right);

[0028] Figure 8 TGA curves of Fe3O4@TAPT-OMePDA and Fe3O4@TAPT-TFPDA.

[0029] Fig. 9 The hysteresis loop diagrams of Fe3O4@TAPT-OMePDA and Fe3O4@TAPT-TFPDA;

[0030] Fig.10 Effects of different factors on the adsorption of CR by Fe3O4@TAPT-OMePDA and Fe3O4@TAPT-TFPDA

[0031] Fig.11 Pseudo-first-order kinetics (a) and pseudo-second-order kinetics (b) model fitting for the adsorption kinetics of Congo red by magnetic COFs;

[0032] Fig.12 Fitting of Langmuir and Freundlich adsorption isotherm models;

[0033] Fig.13The removal rates of different dyes by Fe3O4@TAPT-OMePDA and Fe3O4@TAPT-TFPDA;

[0034] Fig.14 Comparison of adsorption of CR by different adsorbent materials;

[0035] Fig.15 The recycling effect of Fe3O4@TAPT-OMePDA and Fe3O4@TAPT-TFPDA adsorbents;

[0036] Fig.16 Illustration of the synthesis of magnetic COFs materials. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0038] Example 1: Preparation of Fe3O4@TAPT-OMePDA

[0039] like Fig.16 As shown, the preparation of the magnetic nanocomposite material comprises the following steps:

[0040] 2,5-Dimethoxyterephthalaldehyde (MeO-PDA, 58 mg, 0.3 mmol) and 2,4,6-tris(4-aminophenyl)-1,3,5-triazine (TAPT, 72 mg, 0.2 mmol) were placed in a 100 mL pressure bottle, 15 mL of o-dichlorobenzene and 10 mL of n-butanol were added, and the mixture was dispersed evenly by ultrasonication for 10 min. Then, Fe3O4 (150 mg) was added, and the mixture was dispersed evenly by ultrasonication for 20 min. Aniline inhibitor (2 equivalents, calculated relative to the amount of TAPT, 0.4 mmol, 36 μL) was added. Catalyst Fe(NO3)3·9H2O (25 mg, 0.06 mmol) was ultrasonically dissolved in 5 mL of n-butanol, and after dissolution, it was added to the reaction system in batches (2 mL was added first, and after ultrasonication for 5 min, the remaining 3 mL was added). After ultrasonication for 1 h, the mixture was aged in an oil bath at 100 °C for 24 h. After the reaction, the mixture was separated by magnetic separation, washed twice with ethanol, twice with water, once with ethanol, twice with tetrahydrofuran and once with n-hexane (each washing was ultrasonicated for 30 seconds); finally, it was soaked in n-hexane for 30 minutes. The obtained solid product was dried in a vacuum oven at 60°C for 5 hours to obtain the magnetic COFs material Fe3O4@TAPT-OMePDA.

[0041] Example 2: Preparation of Fe3O4@TAPT-TFPDA

[0042] like Fig.16 As shown, the preparation of magnetic nanocomposite materials includes the following steps:

[0043] One of 2,3,5,6-tetrafluoroterephthalaldehyde (TF-PDA, 62 mg, 0.3 mmol) and 2,4,6-tris(4-aminophenyl)-1,3,5-triazine (TAPT, 72 mg, 0.2 mmol) were placed in a 100 mL pressure bottle, 15 mL of o-dichlorobenzene and 10 mL of n-butanol were added, and the mixture was dispersed evenly by ultrasonication for 10 min. Then, Fe3O4 (150 mg) was added, and the mixture was dispersed evenly by ultrasonication for 20 min. Aniline inhibitor (2 equivalents, calculated relative to the amount of TAPT, 0.4 mmol, 36 μL) was added. Catalyst Fe(NO3)3·9H2O (25 mg, 0.06 mmol) was ultrasonically dissolved in 5 mL of n-butanol, and after dissolution, it was added to the reaction system in batches (2 mL was added first, and after ultrasonication for 5 min, the remaining 3 mL was added). After ultrasonication for 1 h, the mixture was aged in an oil bath at 100 °C for 24 h. After the reaction, the mixture was separated by magnetic separation, washed twice with ethanol, twice with water, once with ethanol, twice with tetrahydrofuran and once with n-hexane (each washing was ultrasonicated for 30 seconds); finally, it was soaked in n-hexane for 30 minutes. The obtained solid product was dried in a vacuum oven at 60°C for 5 hours to obtain the magnetic COFs material Fe3O4@TAPT-TFPDA.

[0044] Test example

[0045] The Fe3O4@TAPT-OMePDA prepared in Example 1 and the Fe3O4@TAPT-TFPDA prepared in Example 2 were subjected to characterization experiments and adsorption tests. The specific experimental operations are as follows:

[0046] Experimental reagents

[0047] Congo red (indicator grade), o-dichlorobenzene (98%), n-butanol (ACS), ferric nitrate nonahydrate (99.9% metals basis), tetrahydrofuran (ACS), n-hexane (AR), ethanol (95%), aniline (AR), humic acid, malachite green chloride (biological stain), crystal violet (AR), rhodamine B (AR), rhodamine 6G (95%), neutral red (ACS), methylene blue (98%), chrome black T (indicator grade), sunset yellow (87%), methyl orange (96%), montmorillonite K-10 and graphene were purchased from Aladdin Reagent Co., Ltd.; fluorescein sodium (IND) and Janus Green B (98%) were purchased from Leyan Reagent Co., Ltd.; 2,3,5,6-tetrafluoroterephthalaldehyde (TF-PDA, 98%), 2,5-dimethoxyterephthalaldehyde (MeO-PDA, 97%), 2,4,6-tris(4-aminophenyl)-1,3,5-triazine (TAPT, 95%) were purchased from Bid Pharmaceutical Technology Co., Ltd.; sugarcane bagasse activated carbon, Fe3O4@ZIF-8, Fe3O4@ZIF-67 and Fe3O4@UiO-66-NH2 were all prepared by ourselves. The experimental water was deionized water, and all reagents were used directly without further purification.

[0048] 1. Characterization of Fe3O4@COFs

[0049] The crystal structures of Fe3O4@TAPT-OMePDA and Fe3O4@TAPT-TFPDA were analyzed by XRD;

[0050] The characteristic functional groups of Fe3O4@TAPT-OMePDA and Fe3O4@TAPT-TFPDA were determined by FT-IR;

[0051] The morphology and size of Fe3O4@TAPT-OMePDA and Fe3O4@TAPT-TFPDA were observed by SEM and TEM;

[0052] The specific surface area and pore size distribution of Fe3O4@TAPT-OMePDA and Fe3O4@TAPT-TFPDA were determined by BET;

[0053] The magnetic properties of Fe3O4@TAPT-OMePDA and Fe3O4@TAPT-TFPDA were determined by VSM;

[0054] The thermal stability of Fe3O4@TAPT-OMePDA and Fe3O4@TAPT-TFPDA was analyzed by TG;

[0055] 2. Adsorption experiment

[0056] Taking Congo red (CR) as the target pollutant, 10 mg of magnetic COFs material was added to 25 mL of CR solution with different initial concentrations, and placed in a constant temperature shaker at a speed of 250 rpm for a period of time. After the adsorption, magnetic separation and membrane were performed, and the absorbance value A was measured by UV-visible spectrophotometer. The effects of initial solution concentration, adsorption time, adsorption temperature, initial pH value, ionic strength and humic acid on adsorption were investigated to optimize the adsorption conditions. The final adsorption capacity q e and removal rate R (%) are calculated by formula (1) and formula (2) respectively.

[0057]

[0058] Where: q e is the equilibrium adsorption capacity of the adsorbent (mg / g); C0 and C e is the initial concentration of Congo red and the concentration after adsorption equilibrium (mg / L); V is the volume of the solution (L); m is the mass of the magnetic COFs material used (g); R (%) is the adsorption removal rate.

[0059] Adsorption kinetics experiment. Take 25mL of CR solution with an initial concentration of 400mg / L and add 10mg of Fe3O4@COFs adsorbent. Oscillate at constant temperature at room temperature, and the adsorption time is 5min, 10min, 15min, 20min, 30min, 60min, 120min, and 180min, respectively. Magnetic separation of the mixed solution and determination of the absorbance of the supernatant. The adsorption kinetics data are fitted by the first-order kinetic equation and the second-order kinetic equation, as shown in equations (3) and (4).

[0060] ln(q e -q t )=lnq e -K1t (3)

[0061]

[0062] Where: k1 (1 / min) and k2 (g / mg·min) are the adsorption rate constants of PFO and PSO models, t (min) is the adsorption time, q t (mg / g) and q e (mg / g) are the adsorption capacity of the material at t and equilibrium time, respectively.

[0063] Adsorption isotherm experiment. 10 mg of magnetic COFs adsorbent was added to 25 mL of Congo red solution with an initial concentration of 100-1200 mg / L, and constant temperature oscillation was performed at room temperature for 3 h until the adsorption reached equilibrium. The adsorption data were fitted by the Langmuir adsorption isotherm equation and the Freundlich adsorption isotherm equation, as shown in equations (5) and (6).

[0064]

[0065] Where: q e (mg / g) is the equilibrium adsorption capacity of the material; C e (mg / L) is the equilibrium concentration; q m (mg / g) is the maximum adsorption capacity calculated according to the Langmuir model; K L and K f is the equilibrium constant of the Langmuir and Freundlich models; 1 / n is the heterogeneity factor of the Freundlich model, and its value is generally between 0 and 1.

[0066] 3. Experimental Results

[0067] 3.1 Optimization of synthesis conditions and structural characterization of Fe3O4@COFs

[0068] 3.1.1 Effects of inhibitor dosage, aging temperature and monomer structure on synthesis

[0069] In the process of optimizing the synthesis of magnetic COFs materials, the effects of aniline inhibitor, aging temperature and substituents of aldehyde monomers on the reaction were systematically investigated. First, methoxy-substituted MeO-PDA was used as the aldehyde monomer to investigate the effect of the amount of aniline inhibitor (0 to 5 equivalents). SEM, XRD and BET were used to characterize the morphology, crystallinity and porosity of Fe3O4@COFs materials (Fe3O4@TAPT-OMePDA) obtained with different amounts of aniline. The SEM characterization results showed that with the addition of aniline, Fe3O4@COFs gradually changed from irregular aggregates to a flower-like structure of regular nanosheets interwoven. The flower-like structure of the nanosheets interwoven was most obvious when the amount of aniline inhibitor was 2 and 3 equivalents ( Figure 1 ). When the inhibitor dosage continued to increase to 4 and 5 equivalents, the yield of Fe3O4@COFs decreased significantly, indicating that the inhibition was too strong. At the same time, XRD ( Figure 2 a) and BET( Figure 2 b) The results show that when the amount of aniline added is 2 equivalents, the crystallinity and specific surface area of ​​Fe3O4@COFs are the highest (568m 2 / g). Finally, the Fe3O4@COFs synthesized with different aniline addition amounts were used in the adsorption experiment. The material synthesized with 2 equivalents of aniline had the highest removal rate for CR ( Figure 2c). The addition of an appropriate amount of inhibitor can improve the microstructure of Fe3O4@COFs, but excessive inhibitor will inhibit the formation of COFs. Therefore, the optimal amount of aniline is 2 equivalents, at which the structure and adsorption properties of the material are optimal. This is because the addition of aniline inhibitor increases the dynamic reversibility of the imine bond and promotes the self-correction of crystal defects, thereby forming an ordered, defect-free crystal structure.

[0070] Then, the effect of aging temperature (25-100°C) on the structure and properties of the material was investigated. SEM and XRD ( Figure 3 ) The results show that increasing the aging temperature is beneficial to improving the microstructure and crystallinity of the material. The adsorption experiment also shows that increasing the aging temperature is beneficial to improving the adsorption performance of the material.

[0071] Finally, by adjusting the substituents of the aldehyde monomers, the effects of the substituents on the structural stability of COFs materials were explored, and the versatility and functional group tolerance of the optimized synthesis conditions were investigated. The differences in the reactions of terephthalaldehyde (PDA), MeO-PDA and TF-PDA with different substituents and TAPT were compared. Under the optimized synthesis conditions, the material synthesized from the tetrafluoro-substituted monomer TF-PDA has the best crystallinity, porosity and adsorption properties ( Figure 4 ). However, the structure and performance of materials synthesized with PDA as a monomer have not been significantly improved.

[0072] 3.1.2 Material characterization

[0073] SEM characterization shows that Fe3O4@TAPT-OMePDA is a nanoflower structure composed of nanosheets, and Fe3O4@TAPT-TFPDA is a hydrangea shape composed of small particles of about 70-80nm ( Figure 5 ). FT-IR results show ( Figure 6 ), when the Schiff base condensation reaction between the aldehyde group and the amino monomer formed an imine bond, the characteristic peaks of the aldehyde group and the amino group disappeared in the spectra of Fe3O4@TAPT-OMePDA and Fe3O4@TAPT-TFPDA, but both peaks were at 1578 cm -1 The stretching vibration peaks of imine (C=N) appeared at 587 and 589 cm -1 The stretching vibration peak belonging to the Fe-O bond appeared nearby. The water contact angle test results showed that ( Figure 7 ), the water contact angle of Fe3O4@TAPT-OMePDA is 54.31°, which is a hydrophilic material; the water contact angle of Fe3O4@TAPT-TFPDA is 109.68°, which is a hydrophobic material. TG test shows ( Figure 8), when the temperature rises from 25℃ to 800℃, Fe3O4@TAPT-OMePDA loses 34.47% of its mass, leaving 65.53% of its initial mass; Fe3O4@TAPT-TFPDA loses 23.00% of its mass, leaving 70.00% of its initial mass. The saturation magnetizations of Fe3O4@TAPT-OMePDA and Fe3O4@TAPT-TFPDA were measured by VSM to be 44.05 and 48.52emu / g, respectively ( Fig. 9 ), indicating that the material has good magnetic properties and can be magnetically separated under the action of an external magnetic field.

[0074] 3.2 Adsorption performance

[0075] 3.2.1 Factors affecting adsorption experiments

[0076] Using the strategy of controlling variables, the effects of initial CR concentration, adsorption time, pH, humic acid (HA), temperature and ionic strength on the adsorption performance of two adsorbents (Fe3O4@TAPT-OMePDA and Fe3O4@TAPT-TFPDA) were systematically investigated. Fig.10 ). It was determined that pH, HA, temperature and ionic strength had little effect on the adsorption performance of the material, indicating that the material has good adaptability to changes in external factors. The final adsorption conditions were: adsorption equilibrium time of 120 minutes, adsorption temperature of 25°C, pH of the solution's initial pH, and CR initial concentration of 400 mg / L.

[0077] 3.2.2 Adsorption kinetics and adsorption isotherm studies

[0078] The experimental data on the effect of time were fitted using the nonlinear forms of pseudo-first-order (PFO) and pseudo-second-order (PSO) kinetic models ( Fig.11 The experimental data on the effect of concentration were fitted using the Langmuir and Freundlich adsorption isotherm models ( Fig.12 ).from Fig.11 As can be seen from Table 1, the PSO model has a higher degree of fit than the PFO model for both adsorbents (Fe3O4@TAPT-OMePDA and Fe3O4@TAPT-TFPDA) (correlation coefficient R 2 = 0.99436 and 0.99781). Therefore, the adsorption of CR by the two magnetic COFs materials is more consistent with the PSO model, which is mainly chemical adsorption. Fig.12 As can be seen from Table 2, the adsorption isotherm fitting results of the two materials show that the Langmuir model is better than the Freundlich model (R 2=0.98101 and 0.98662). This indicates that the adsorption of CR by these two magnetic COFs materials is more consistent with the Langmuir model and is a monolayer adsorption. Moreover, the maximum adsorption capacities of the two magnetic COFs materials calculated by the Langmuir model are as high as 1603.54 and 1968.83 mg / g, respectively.

[0079] Table 1. Fitting parameters of pseudo-first-order (PFO) and pseudo-second-order (PSO) kinetic models

[0080]

[0081] Table 2. Langmuir and Freundlich isotherm adsorption model fitting parameters

[0082]

[0083] 3.2.3 Adsorption selectivity and comparative experiments

[0084] Adsorption selectivity. The adsorption selectivity of magnetic COFs materials was investigated by comparing the adsorption effects of different dyes. The initial concentration of various anionic and cationic dyes was 100 mg / L, and other adsorption conditions remained unchanged. The results are as follows: Fig.13 As shown. Both Fe3O4@TAPT-OMePDA and Fe3O4@TAPT-TFPDA have the best adsorption effect on the anionic dye CR, with almost 100% removal; the two materials have the second best adsorption effect on malachite green, rhodamine B, Janus green B, and chrome black T, with a removal rate of about 50-80%; the adsorption effect of the remaining other dyes is poor. From a structural point of view, the aromatic system in the structure of CR, Janus green B and chrome black T, which have relatively good adsorption effects, is relatively large. It is possible that the π-π interaction between the aromatic rings in the magnetic COFs material and the aromatic rings in the dye molecules plays an important role in the adsorption.

[0085] Comparative experiment. Using Congo red as a model pollutant, the adsorption performance of different adsorbents was investigated under the same conditions. Common activated carbons from graphene, montmorillonite and bagasse, and magnetic MOFs materials (Fe3O4@ZIF-8, Fe3O4@ZIF-67 and Fe3O4@UiO-66-NH2) were selected for comparative experiments. The results are as follows: Fig.14 As shown. It can be seen that the adsorption performance of the magnetic COFs material we synthesized is significantly better than other adsorbents.

[0086] 3.3 Recycling

[0087] After adsorbing Congo red dye, in order to achieve the recycling of the adsorbent, it is necessary to select a suitable desorption solvent to desorb the adsorbed Congo red, thereby achieving the regeneration of the magnetic COFs material. Ethanol, ethanol-NaOH (v / v, 9:1) and ethanol-HCl (v / v, 9:1) were selected as desorption solvents for testing. Finally, ethanol-NaOH (0.1 mol / L) (volume ratio of 9:1) was the best desorption solvent. After 5 adsorption-desorption cycles of the two materials, the results are as follows Fig.15 As shown in the figure, the two magnetic COFs materials (Fe3O4@TAPT-OMePDA and Fe3O4@TAPT-TFPDA) have no significant effect on the removal rate and adsorption capacity of CR, indicating that the two magnetic COFs materials we synthesized have strong regeneration ability.

[0088] IV. Conclusion

[0089] The present invention obtains magnetic COFs materials (Fe3O4@TAPT-OMePDA and Fe3O4@TAPT-TFPDA) with significantly improved porosity, crystallinity and adsorption performance by optimizing the synthesis conditions (aniline inhibitor dosage and synthesis temperature), and is used to adsorb and remove Congo red (CR) in water. Experiments show that the adsorption capacity of Fe3O4@TAPT-OMePDA and Fe3O4@TAPT-TFPDA for CR is as high as 1603.54 mg / g and 1968.83 mg / g. The adsorption of CR by the two adsorbents conforms to the quasi-second-order kinetic model and the Langmuir isotherm model, and belongs to monolayer chemical adsorption. Compared with the adsorbents in the prior art, Fe3O4@TAPT-OMePDA and Fe3O4@TAPT-TFPDA have high porosity, high adsorption efficiency, good selectivity and good reuse rate, which has practical reference significance for the actual treatment of printing and dyeing wastewater in the future.

[0090] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A magnetic nanocomposite material used as an adsorbent in removing organic dyes from water, characterized in that: The magnetic nanocomposite material is one of Fe3O4@TAPT-OMePDA and Fe3O4@TAPT-TFPDA.

2. The use of a magnetic nanocomposite material as an adsorbent in removing organic dyes from water according to claim 1, characterized in that: The preparation method of the magnetic nanocomposite material is as follows: Place the aldehyde monomer and the amino monomer in a 100 mL pressure bottle, add o-dichlorobenzene and n-butanol as reaction solvents, ultrasonicate for 5-15 minutes to make them dispersed evenly, then add aniline as an inhibitor, add Fe3O4 as a magnetic core, and ultrasonicate for 10-30 minutes to make Fe3O4 dispersed evenly; Fe(NO3)3·9H2O was ultrasonically dissolved in n-butanol as a catalyst, and then added to the pressure bottle reaction system in batches after dissolution, and ultrasonically reacted for 1 hour, and then aged in an oil bath at 80-120°C for 24 hours; After the reaction, the mixture was separated by magnetic separation, washed twice with ethanol by ultrasonic wave for 20-40s, then washed twice with water by ultrasonic wave for 20-40s, then washed once with ethanol by ultrasonic wave for 20-40s, then washed twice with tetrahydrofuran by ultrasonic wave for 20-40s and washed once with n-hexane by ultrasonic wave for 20-40s; Finally, the mixture is immersed in n-hexane for 20-40 minutes, and the solid product is dried in a vacuum drying oven at 50-70° C. for 4-6 hours to obtain the magnetic nano-composite material.

3. The use of a magnetic nanocomposite material as an adsorbent in removing organic dyes from water according to claim 2, characterized in that: The aldehyde monomer is one of 2,5-dimethoxyterephthalaldehyde and 2,3,5,6-tetrafluoroterephthalaldehyde.

4. The use of a magnetic nanocomposite material as an adsorbent in removing organic dyes from water according to claim 2, characterized in that: The amino monomer is 2,4,6-tris(4-aminophenyl)-1,3,5-triazine.

5. The use of a magnetic nanocomposite material as an adsorbent in removing organic dyes from water according to claim 2, characterized in that: The ratio of the amount of the aldehyde monomer (mmol), the amount of the amino monomer (mmol), the amount of aniline (mmol), the amount of Fe(NO3)3·9H2O (mmol), the mass of Fe3O4 (g), the volume of o-dichlorobenzene (mL) and the volume of n-butanol (mL) is 0.3:0.2:0-1:0.06:0.15:15:

15.

6. The use of a magnetic nanocomposite material as an adsorbent in removing organic dyes from water according to claim 3, characterized in that: The purity of the 2,5-dimethoxyterephthalaldehyde is 97%.

7. The use of a magnetic nanocomposite material as an adsorbent in removing organic dyes from water according to claim 3, characterized in that: The purity of the 2,3,5,6-tetrafluoroterephthalaldehyde is 98%.

8. The use of a magnetic nanocomposite material as an adsorbent in removing organic dyes from water according to claim 4, characterized in that: The purity of the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine is 95%.

9. The use of a magnetic nanocomposite material as an adsorbent in removing organic dyes from water according to claim 5, characterized in that: The purity of the aniline is AR, the purity of o-dichlorobenzene is 98%, the purity of n-butanol is ACS, and the purity of Fe(NO3)3·9H2O is 99.9% metals basis.

Citation Information

Cited By

  • Organic pollutant water treatment adsorption material and preparation method thereof

    CN121467000A

  • Organic contaminant water treatment adsorbent material and method of making same

    CN121467000B

  • Preparation method of magnetic solid-phase extraction material and application of magnetic solid-phase extraction material to trace detection of PFASs

    CN121669199A